Encapsulation of protease from Aspergillus oryzae and lipase from Thermomyces lanuginoseus using alginate and different copolymer types - Thu, Truong Thi Mong; Krasaekoopt, Wunwisa (Agriculture and Natural Resources, 2016)
Although the application of enzymes in food as a food processing aid and enzyme supplement is of interest and widely used, the enzymes can be easily deactivated or lose their activity due to many causes such as pH and moisture as well as through the introduction of incompatible ingredients during food processing and storage. These problems can be solved by the encapsulation technique, especially in a gel matrix. The influences were studied of the alginate concentration, types of copolymer and their concentrations on the bead size, encapsulation yield (EY), encapsulation efficiency (EE), leakage and the retention of enzyme activity during storage period of encapsulated protease from Aspergillus oryzae and lipase from Thermomyces lanuginosus beads. A solution of purified protease or lipase was encapsulated in calcium alginate-chitosan beads (CACB), calcium alginate-xanthan gum beads (CAXB) and calcium alginate-maltodextrin beads (CAMB) using the extrusion method. Increasing the alginate and copolymer concentrations in the solution increased the bead size, EY, EE and the retention of enzyme activity during the storage period and reduced leakage of both the encapsulated protease and lipase. In addition, different types of copolymer significantly (p ≤ 0.05) affected these properties of both encapsulated enzymes. Furthermore, protease encapsulated using 2.0% alginate and 0.2% chitosan provided the highest EY (81.7%) and EE (77.2%) with a bead size of 1.85 mm and 8.1% leakage. The retention of encapsulated protease activity and the shelf-life of encapsulated enzyme which was expressed as half-life, the time required for the enzyme activity to decrease by half (thalf life) were 75.8% and 27.2 wk, respectively after storage at 4 C for 10 wk. For lipase, encapsulation using 2.0% alginate and 0.4% xanthan gum provided the highest EY (42.5%) and EE (43.9%) and the bead size and leakage were 1.81 mm and 6.2%, respectively. The retention of encapsulated lipase activity and the thalf life were 77.9% and 27.8 wk, respectively after storage at 4 oC for 10 wk. CACB was a suitable complex polymer for encapsulating protease while CAXB was suitable for lipase. EY and EE values of CACB-protease were higher than those of CAXB-lipase. Therefore, the encapsulation method, gelling conditions and interactions between carriers and lipase should be further studied.